Southeast Asian ecocriticism theories, practices, prospects - Ryan, John (John Charles) (Lanham Lexington Books, 2018)
"This book offers a timely exploration into the rapidly growing field of ecocriticism and gives prominence to the writers, creators, theorists, traditions, concerns, and landscapes of Southeast Asia. The contributors emphasize the transnational flows between Southeast Asian countries and Australia, England, Taiwan (Formosa), and the United States"--Provided by publisher.
An introduction to Southeast Asian ecocriticism / John Charles Ryan -- Ecocriticism, hermeneutics, and the vanishing elephants of Thailand / Ignasi Ribâo -- Filipino ecological imagination : Typhoon Yolanda, climate change, and imperialism in Philippine poetry and prose / Jeffrey Santa Ana -- Imaging indigenous relationships with nature : the case of Igorot music videos / Jason Paolo R. Telles -- Terror, narrative, and ecology in Merlinda Bobis's novel Fish-hair woman / Chitra Sankaran -- Environmental consciousness in the ecopoetry of Angkarn Chanthatip : a reading of Sieng sontana jaak panang tham from Hua jai hong tee ha (The fifth chamber of the heart) / Chaiyon Tongsukkaeng -- Sense of place and nostalgia for homeland in Rewat Phanphiphat's poetry / Thanya Sangkhaphanthanon -- From padauk to hyacinth : literary botany, the agency of plants, and the contemporary poetry of Myanmar / John Charles Ryan -- Listening to nature, rethinking the past : a reading of the representations of forests and rivers in post-war Vietnamese narratives / Tran Ngoc Hieu and Dang Thi Thai Ha -- Sowing seeds : phytocriticism and the botanical dimensions of Indonesian literature for children and young adults / Richard Li and John Charles Ryan -- Transnational paradigm : teaching Leslie Marmon Silko's Ceremony in Thailand / Wasinrat Nualsiri -- Economics, ecology, and desire : delineations of Formosa and neighboring Southeast Asian countries in three nineteenth-century travelers' natural histories / Lu Liru -- Epilogue : Ziggy Stardust and the Irrawaddy dolphin : prospects for a transboundary ecocriticism in Southeast Asia / John Charles Ryan.
Includes bibliographical references and index.
Keywords: Ecocriticism -- Southeast Asia; Southeast Asian literature -- History and criticism; Environmental literature -- Southeast Asia; Ecology in literature; Human ecology in literature; Southeast Asia -- In literature